The Relationship between Basic and Advanced Financial Literacy Index and Lecturer Financial Planning - Soejono, Fransiska; Mendari, Anastasia Sri (JDM (Jurnal Dinamika Manajemen), 2020)
Aims of this study are to discover the way lecturers in Palembang manage their financial planning and to analyze the relationship between the financial literacy index and financial planning. The data of this study were analyzed by conducting descriptive analysis and using the pearson correlation coefficient in the testing a hypothesis. Respondents in this study were as many as 153 people. For collecting data, a survey has been conducted by sending questioners. Based on the survey, generally, lecturers in Palembang have implemented the steps of their financial planning and debt management in a good way, and that the lecturers recognize the importance of insurance, but, the survey also pointed out that the lecturers do not have a piece of sufficient knowledge to determine a particular product of insurance that suits their need. The investment activity of the lecturers is considered lacking since most of the lecturers have no plan on preparing pension funds and inheritance of their own despite their knowledge of the importance of preparing them. It has been figured out that there is a relation between basic financial literacy and financial planning. Advanced financial literacy also has a relation to financial planning. This study implicates that a good understanding of financial literacy related to improvement in financial planning so that it needs a bigger effort from the respondents for improving their awareness on the importance of financial planning.